Progression From Subclinical Inflammation to Overt Spondyloarthritis in First‐Degree Relatives of Patients in Association With HLA–B27: The Pre‐Spondyloarthritis Cohort. Issue 12 (7th September 2022) - de Jong, Henriëtte M. Y.; de Winter, Janneke J. H.; van der Horst‐Bruinsma, Irene E.; van Schaardenburg, Dirk‐Jan; van Gaalen, Floris A.; van Tubergen, Astrid M.; Weel, Angelique E. A. M.; Landewé, Robert B. M.; Baeten, Dominique L. P.; van de Sande, Marleen G. H.
Abstract : Objective: As first‐degree relatives (FDRs) of HLA–B27–positive patients with axial spondyloarthritis (SpA) have an increased risk of developing axial SpA, the objectives were 1) to evaluate the presence of highly specific imaging features as well as clinical signs of SpA at baseline and after 1 year of follow‐up, and 2) to describe the evolution toward clinical disease within 1 year of follow‐up in a cohort of seemingly healthy FDRs of HLA–B27–positive axial SpA patients. Methods: The Pre‐SpA cohort is a 5‐year prospective inception cohort of seemingly healthy FDRs of HLA–B27–positive axial SpA patients. Clinical and imaging features were collected and recorded. Results: At baseline, 19% of the FDRs reported inflammatory back pain, 32% current arthralgia, 3% arthritis (ever), 5% enthesitis (ever), and 1% dactylitis (ever), and 3% had an extraarticular manifestation. C‐reactive protein level was elevated in 16%, and erythrocyte sedimentation rate was elevated in 7%. On magnetic resonance imaging (MRI) views of sacroiliac joints, 10% had a Spondyloarthritis Research Consortium of Canada score of ≥2, 4% had a score of ≥5, and 4% had deep lesions. In total, 1% fulfilled the modified New York criteria for radiographic sacroiliitis. Clinical, MRI, and acute phase findings were equally distributed between HLA–B27–positive and –negative FDRs. After 1 year of follow‐up, clinical parameters did not change on the group level, but 6% of the FDRs were clinically diagnosed with axial SpA, of whom 86% were HLA–B27–positive. Conclusion: Features associated with SpA or imaging abnormalities were found in up to 32% of seemingly healthy FDRs, with an equal distribution between HLA–B27–positive and –negative FDRs. Progression to clinical axial SpA within 1 year of follow‐up was mainly observed in HLA–B27–positive FDRs.